PENGARUH MODEL PEMBELAJARAN INDEX CARD MATCH TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA TERPADU - Toni Hidayat; Amaano Fau; Darmawan Harefa (Universitas Nias Raya, 2023)
The purpose of this study was to determine the effect of the index card match learning model on students' cognitive learning outcomes in the Integrated Science subject for class VIII SMP Negeri 1 Toma in the 2022/2023 academic year. This study uses a quantitative approach with a quasi-experimental method. The sample of this research is class VIII-A with 30 students and class VIII-B with 31 students. The instrument used is the learning achievement test which is divided into two, namely the initial test and the final test and documentation. Based on the results of data processing that has been carried out by researchers, the following results are obtained: